2016
DOI: 10.1093/cid/ciw612
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic CMV Replication During Early Human Immunodeficiency Virus (HIV) Infection Is Associated With Lower CD4/CD8 Ratio During HIV Treatment

Abstract: Background. A low CD4/CD8 ratio in human immunodeficiency virus (HIV)-infected individuals is associated with inflammation and higher risk of non-AIDS morbidity and mortality. In this study, we investigated the effect of subclinical cytomegalovirus (CMV) and Epstein-Barr virus (EBV) replication on CD4 + and CD8 + T-cell dynamics when antiretroviral therapy (ART) is started during early infection.Methods. We investigated 604 peripheral blood mononuclear cell samples from 108 CMV-and EBV-seropositive HIV-infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 34 publications
2
30
0
1
Order By: Relevance
“…A recent paper reported that even among individuals who started ART early (with high CD cell count), asymptomatic CMV reactivation was associated with slower CD4/CD8 recovery. [20] Although CMV has not been reported as a significant cause of death in previous studies, we agree that CMV viremia could be associated with direct CMV pathogenic effects underestimated in their contribution to death. CMV viremia could be a cause, or a consequence, of poor immune function.…”
Section: Discussionsupporting
confidence: 63%
“…A recent paper reported that even among individuals who started ART early (with high CD cell count), asymptomatic CMV reactivation was associated with slower CD4/CD8 recovery. [20] Although CMV has not been reported as a significant cause of death in previous studies, we agree that CMV viremia could be associated with direct CMV pathogenic effects underestimated in their contribution to death. CMV viremia could be a cause, or a consequence, of poor immune function.…”
Section: Discussionsupporting
confidence: 63%
“…Several studies demonstrate links between reservoir size, chronic inflammation, and earlier onset of age-related diseases, despite long-term, successful viral suppression (reviewed in reference 23). Similarly, persistent replication by the chronic viral infection CMV, a herpesvirus, is associated with inflammation, age-related disease, and, in PLWH, larger HIV reservoirs (7,22,24,25,28).…”
Section: Discussionmentioning
confidence: 99%
“…Associations with CD4/CD8 ratios remained at V1 and V3, but not thereafter. This disconnect may reflect clearance of CMV DNA from some patients in our study, as CMV DNA detected in PBMC and the patient's age associated with CD4/CD8 ratios over 3 years when ART was initiated in early HIV disease (24). Here levels of CMV lysate antibody at V6 and V12 correlated inversely with CD4/CD8 ratios, directly with proportions of CD8 T-cells and inversely with proportions of CD4 T-cells.…”
Section: Discussionmentioning
confidence: 72%